DEVELOPING CRITICAL THINKING AND COMMUNICATIVE SKILLS IN THE EDUCATIONAL PROCESS - Gulomjon Gaibbaev, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This study examines the development of critical thinking and communicative skills in the educational process. Modern education emphasizes not only knowledge acquisition but also the formation of essential competencies necessary for students to succeed in complex and dynamic environments. The research identifies effective methods, including problem-based learning, group discussions, and project-based activities, that enhance students’ analytical, collaborative, and communication abilities. Results show that implementing interactive and innovative teaching strategies significantly improves students’ competence levels. The study concludes with recommendations for integrating technology and active learning techniques to foster critical thinking and communication skills in learners.